Locutionary, Illocutionary and Perlocutionary Speech Acts in the Short Story of Aini and Our Play by Hasan Aspahani - Mayvina Exva Anggraeni; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Speech acts are included in the science of pragmatics in which one learns the utterances or utterances of a person against his interlocutor. Speech acts sometimes create different meanings between the speaker and the interlocutor. It is customary in Indonesian society that the longer the speech, the higher the level of speech acts or the level of politeness, conversely if the utterances are short, then the level of speech acts or the level of politeness is less. Tutut is divided into three, namely, locution, illocutionary and perlocutionary. Because there are several kinds of speech acts, it is necessary to have an in-depth study of a person's speech. The researcher chose short stories as the object to be analyzed. Short stories use everyday language or standard language so that they produce different meanings or different tones when reading. Speech activities can occur anywhere if there is an interlocutor. A locutionary speech act is an utterance in the form of a statement. Illocutionary is an utterance in which there is information that the speaker wants to convey. Perlocutionary speech is a speech that has an effect or influence on the listener or the interlocutor.